(3cJGH eSFdI Ydh Gddg JYGdis - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3hQhi GdMGaX YHO GdZfi hTjN GdESdGe CHh GdMSf GdgcGQi hZjQgG Yf GdEeGe CHj YHO Gddg GdTGaYi QMeg Gddg bGd Gdbhd ai GdSfI GdJi CfG YdjgG hQCjJ Cgd GdMOjK YdjgG s
(3BNQgG (B:s
(3hEf GdbQBf cdGe Gddg efg HOGA HdG cjajI bhdkG hGfRdg Ydi fHjg Udi Gddg Ydjg hSde hMjkG hUObJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs